Values in higher education teaching - Harland, Tony 1955-; Pickering, Neil (Routledge, 2011)
'Values in Higher Education Teaching' explores the way in which teaching, research, learning and higher education are a values enterprise and that an exploration of values is necessary to work out the full purposes of a higher education to guide practices and help academics understand academic work.